DRIVERS AND OBSTACLES OF THE REMANUFACTURING PRACTICES IN CHINA: AN EMPIRICAL STUDY - Wang, Yacan; Zhang, Liang; Zhang, Chunhui; Jeeva, Ananda (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
Remanufacturing is one of the prioritized sectors that pushes sustainability forward, and has been vigorously promoted by two rounds of pilot programs in China. Using a survey conducted in 7 Chinese pilot remanufacturing enterprises involving 190 respondents, we empirically identify the current situation and explore the influential factors of the remanufacturing industry in China. The results of principal component factor analysis indicate that enterprise strategy factors as well as policy and technical factors are the major drivers to the development of the remanufacturing industry while the policy, economic factors and industry environmental factors are the major barriers. This is the first empirical study to explore the influencing factors of the remanufacturing industry in China. The results provide preliminary reference for government and industry to further develop mechanism to promote remanufacturing practice in China.